How To Packaging Form, Price On Packaged Tea Purchase Decisions ? - Winarti , Winarti; Gazali, Agus Umar; Bahri, Syamsul; Nurhadi, Nurhadi (STIE Amkop Makassar, Indonesia, 2024)
The phenomenon of tea is one of the most widely consumed drinks by the people of our homeland apart from mineral water, especially after the trend of drinking tea with various kinds of flavors and tea variants is not only in demand by the elderly but almost all groups, be it old, young or old. even children like tea. Various product shapes such as squares, ovals, ovals or even rounds greatly affect sales because shape also influences the selling price. This study aims to see how much influence sales have on different forms of tea. The population in this study were college students and also employees in the city of Makassar. In this study there were 100 respondents and the sample was taken using simple random sampling technique. Data analysis technique using descriptive verification method. The results showed that the form of packaging greatly influences the price and purchasing decisions. The research results also show that the relationship between packaging form, price and purchase decision is in the high category